(untitled) (Studia Prawnicze / The Legal Studies, 1981)
This article analyze characteristic features of bureaucratic decision-makinng process and its relation to bureaucratic organization of state apparatus of general administration. For this process rationality, legality and standarization of decisions are characteristic. Rationality of a decision is postulated by contemporary culture. A decision is rational internally when it is justified by knowledge and preferences of the person making decision; it is externally rational when according to the critic these premises are correct. Bureaucracy favours making decisions internally rational by relating decident’s knowledge to his status in the hierarchy of appa- ratus the and by preferences expressed in stereotype of “bureaucratic personality”. Uniformity of knowledge and preferences helps uniformity of decisions. Criticism of a decision from external point of view shows the difference between the knowledge of the decident and the paradigm of science, and the domination of ritualistic and conformistic attitudes not favouring innovation. Bureaucracy favours making legalistic decisions in the sense that the are conformable to the rules of decisions accepted within the apparatus. These rules include binding laws and internal rules. The latters are supposed to eliminate decision-lacunae which in result leads to formality of decisions and little adapta- bility conflicting with their efficacy. Bureaucracy favours making typical decisions which do not reflect indi- viduality of particular cases. Internal rules typify the decisions unifying them within the scope of the lee-ways left by binding laws. The criticism of bureaucracy accepts the necessity of its existence as organization and decision-making process, as well as its disfunctions. That is why the Author analysis the following relations between: the structure of the apparatus and independent character of a decision; legalism and efficacy of a decision: certainty of a decision and its individualization; decisional-lee-ways and responsibility.